Preparation and Characterization of Cellulose Nanocrystal Extraction From Pennisetum hydridum Fertilized by Municipal Sewage Sludge via Sulfuric Acid Hydrolysis - Yu, Xiaoshan; Jiang, Yu; Wu, Qitang; Wei, Zebin; Lin, Xianke; Chen, Yangmei (Frontiers in Energy Research, 2021)
Pennisetum hydridum has been used to make regenerated cellulose membrane, but it has not been shown that it can be used to make cellulose nanocrystals (CNC). Due to a high specific surface area, CNC has been widely used in the treatment of municipal sewage and wastewater polluted by heavy metals. Here we show CNC were prepared from Pennisetum hydridum fertilized by municipal sewage sludge (MSS) by sulphuric acid hydrolysis in different acid concentrations (40 % 65 %), temperature (room temperature 55℃) and reaction time (50 min 120 min). The results showed that the obtained CNC possessed stable dispersion in water. The length of CNC reached 272.5 nm under the condition of room temperature (RT) - 65 % - 120 min, and the diameter was within 10 nm. Furthermore, Fourier transform infrared (FTIR) showed that the CNC still kept cellulose type I structure. The crystallinity of CNC increased maximum by 18.34% compared with delignified Pennisetum hydridum fiber. Thermogravimetric (TG) illustrated the thermal stability of CNC was lower than that of delignified Pennisetum hydridum fiber due to introduction of sulfate groups in the cellulose. This study demonstrated that it might be a suitable raw material of CNC from Pennisetum hydridum fertilized by MSS. It is meaningful for resource utilization of MSS and Pennisetum hydridum.